ORGANIZATIONAL AND ECONOMIC ASPECTS OF IMPROVING SUBURBAN RAILWAY TRANSPORTATION - A. V. Kurbatova; D. A. Plotnikova (Вестник университета)
The features of management of domestic railway transport at different stages of its development have been disclosed. The main principles and conditions of structural reform in the industry have been formulated. The main models of management of the railway complex, principles and features of the organization of suburban railway communication in different countries have been characterized. Statistical data on suburban rail transport on the infrastructure of JSC «Russian Railways», confirming their importance and significance for the Russian Federation, have been adduced. The economic results of the activity of domestic suburban passenger companies have been considered. The shortcomings of the existing methodology for assessing the financial condition of suburban passenger companies have been indicated. The proposals to improve the current methods of calculations taking into account the conditions of prospective development of companies have been given. The scheme of scientific and methodical approach to the analysis of economic condition of the suburban passenger companies, including set of procedures of calculated and analytical character, has been offered.